IDENTITAS DAN KEARIFAN LOKAL “ISLAM SAMIN” DI ERA GLOBAL - Ismail Yahya (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2009)
This research aims firstly; to describe the construct of identity and local wisdom of Samin community in Kemantren village, Kedungtuban, Blora, Central Java, secondly; to explain change and continuity of their identity and local wisdom facing globalization. This research is descriptive qualitative, synthesis of library and field research. Library research studies the teaching and history of Saminism in general. Field research digs their identity and local wisdom through observation and unstructured interview. Informants were chosen purposively. The research was conducted on June-August 2007. The results are firstly; the construct of identity of Saminism comprises the identity of historicity, dress, language, house, marriage, and in agriculture. Their local wisdom was seen in personal attitude, social harmony attitude, and attitude towards nature. Secondly; there are factors and actors involving in change of their identity and local wisdom. There are external and internal factors, structural and cultural actors. The continuity of their identity and local wisdom goes through internalization, limitation of education, self sufficiency, and endogamy.